Two new species of Chromadoridae (Chromadorida: Nematoda) from the East China Sea - Huang, Yong; Gao, Qun (Zootaxa, 2016)
Two new species of Chromadoridae, a family of free-living marine nematodes, are described from intertidal sediments of the East China Sea. Ptycholaimellus pirus sp. nov. is characterized by having a cuticle with six longitudinal rows of double dots and long somatic setae, relatively long cephalic setae, a pear-shaped terminal pharyngeal bulb occupying less than 30% of pharyngeal length, and an elongate conical tail. The new species is distinguished from all related species by the unique character of the cuticle, with six longitudinal rows of horizontal double dots, and the pear-shaped terminal pharyngeal bulb. Hypodontolaimus ventrapophyses sp. nov. is characterized by having a cylindrical body with a slightly expanded anterior end and a conical tail, a homogeneous cuticle with lateral differentiation of two longitudinal rows of larger dots, a well developed pharynx with oval-shaped buccal bulb and terminal bulb, and a large ventral gland. Males have slender, strongly curved spicules and a gubernaculum with a ventral apophysis, and precloacal supplements are absent. The new species differs from all related species in this genus by the structure of the gubernaculum, which has a ventral apophysis.